Endoscopic Full-Thickness Resection for Gastric Subepithelial Lesions Arising from the Muscularis Propria - Ah Lon Jung; Sang Wook Park; Gun Young Hong; Hyeong Chul Moon; Seo Joon Eun (Korean Society of Gastrointestinal Endoscopy, 2021)
Most cases of gastric subepithelial lesions follow a good clinical course; however, some lesions progress to malignant tumors, and treatment of tumors with a high risk of malignancy is essential. Surgical excision has been the primary treatment for tumors originating from the propria muscle layer, but it has the disadvantages of being invasive and causing postoperative functional abnormalities. With the development of endoscopic techniques and instruments, the role of endoscopic resection, which is a less invasive method for the removal of gastric subepithelial lesions, has been attracting attention. We performed an endoscopic full-thickness resection for 8 patients with gastric subepithelial lesions originating from the muscularis propria. No fatal complications occurred. Our findings suggest the need to develop various devices for resection and closure and to accumulate further experience through additional studies to prevent complications and specimen loss.